The Analysis of Indonesian Electronic Transaction Tax (ETT) Under WTO Law - Taufiq Adiyanto (Law Development Journal, 2023)
The existing international tax system, which is regulated by two fundamental principles—source- and residence-based principle, is no longer adequate for regulating corporate and digital service taxation. Act No. 2 of 2020 provides a legal basis for the imposition of Electronic Transaction Tax (ETT) on electronic commerce conducted by foreign merchants, foreign service providers, and/or foreign trade, which meet the provisions of having a significant economic presence such as Google, Amazon, Facebook, and Apple (GAFA). With the unilateral measure by Indonesia, it can be considered as having created a new tax policy outside the tax treaty and becoming an issue of a trade war between countries. Regarding Indonesia's GATS obligations, there is potential for an ETT to violate the obligations of national treatment and MFN. However, such tax can be justified under available exceptions in GATS if Indonesia conducts certain legal adjustments on ETT design.